2023
DOI: 10.1007/s11160-023-09799-y
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring marine fishes using underwater video techniques in the Mediterranean Sea

Melina Nalmpanti,
Anna Chrysafi,
Jessica J. Meeuwig
et al.

Abstract: The use of underwater video techniques has expanded rapidly in ecological studies and is particularly desirable in protected areas since the method does not impact the habitat or remove fish. The Mediterranean Sea is a biodiversity hotspot under high anthropogenic pressure and consequently, non-destructive and non-extractive techniques for fish monitoring are advantageous. Here, we review 110 publications that used underwater video in fish-related studies in the Mediterranean basin. The most common technique u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 159 publications
(111 reference statements)
0
2
0
Order By: Relevance
“…Sward et al (2019) provided a systematic review of ROV surveys for visually assessing fish assemblages. Nalmpanti et al (2023) reported that ROVs were the most common visual survey tool used in the Mediterranean Sea (33% of surveys), followed by Remote Underwater Video (RUV) systems (20%), Diver Operated Video (DOV) systems (20%) and Baited Remote Underwater Video (BRUV) systems (19%). Although HOV and ROV tools can provide information about fish community compositions and habitat associations, they are expensive.…”
Section: Introductionmentioning
confidence: 99%
“…Sward et al (2019) provided a systematic review of ROV surveys for visually assessing fish assemblages. Nalmpanti et al (2023) reported that ROVs were the most common visual survey tool used in the Mediterranean Sea (33% of surveys), followed by Remote Underwater Video (RUV) systems (20%), Diver Operated Video (DOV) systems (20%) and Baited Remote Underwater Video (BRUV) systems (19%). Although HOV and ROV tools can provide information about fish community compositions and habitat associations, they are expensive.…”
Section: Introductionmentioning
confidence: 99%
“…Remote or diver-operated underwater videos have been increasingly used by scientists and ecosystem managers to monitor fishes for the last decade across the Mediterranean Sea (Nalmpanti et al, 2023). We believe that our DLAs will be useful for ecosystem managers to accelerate the analysis of videos collected during those NIS monitoring programmes, ensuring detection of Siganus spp.…”
Section: Discussionmentioning
confidence: 99%